Memorising the Mutiny: Felice Beato’s Lucknow Photographs - Claire Bowen (Cahiers Victoriens et Edouardiens)
The best known collections of nineteenth century war photographs are those of Mathew Brady (the Civil War) and Roger Fenton (the Crimea). The war pictures of Felice Beato are less familiar and contemporary interest in his work is concentrated on his later Japanese photographs. Before moving to Japan, and following a period in the Crimea where, with James Robertson, he took over the work of Fenton, Beato spent two years in India. His initial purpose seems to have been to complete a commission from the British War Office, given to himself and Robertson, to make pictures of the sites of the Mutiny. Commission or not, from March 1857—that is to say, after the most intense periods of military action in the city—Beato photographed Mutiny sites in Lucknow, Delhi and Cawnpore. Prints of Beato’s photographs were sold in India and later in Britain as records of the Mutiny. The article approaches Beato’s Mutiny photographs, especially those made in Lucknow in the aftermath of the sieges and the relief campaigns, from two points of view. Firstly, they are considered from a practical point of view as the product of specific commissioning, reproduction and distribution structures and strategies. Secondly, Beato’s pictures—like all war pictures—inevitably raise questions about the reliability of the photograph and about the expectations of the public that buys them. His work is considered in terms of subject choices and possibilities and the technical constraints of the period. The place of Beato as the first “faker” of photographs in the interests of sensationalism is also discussed.